2015
DOI: 10.7314/apjcp.2015.16.10.4347
|View full text |Cite
|
Sign up to set email alerts
|

Association of GSTP1 and RRM1 Polymorphisms with the Response and Toxicity of Gemcitabine-cisplatin Combination Chemotherapy in Chinese Patients with Non-small Cell Lung Cancer

Abstract: Background: Previous studies showed that genetic polymorphisms of glutathione S-transferase P1 (GSTP1) were involved in glutathione metabolism and genetic polymorphisms of ribonucleotide reductase (RRM1) were correlated with DNA synthesis. Here we explored the effects of these polymorphisms on the chemosensitivity and clinical outcome in Chinese non-small cell lung cancer (NSCLC) patients treated with gemcitabine-cisplatin regimens. Materials and Methods: DNA sequencing was used to evaluate genetic polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
(24 reference statements)
2
7
0
Order By: Relevance
“…The study characteristics of the 28 articles included, all were candidate gene studies published between 2008 and 2017, are shown in Table 1 . Most were cohort studies (Wang et al, 2008 ; Filipski et al, 2009 ; Goekkurt et al, 2009 ; Chen et al, 2010 ; Khrunin et al, 2010a , 2012 , 2014 ; KimCurran et al, 2011 ; Tzvetkov et al, 2011 ; Erculj et al, 2012 ; Iwata et al, 2012 ; Windsor et al, 2012 ; Xu et al, 2012 , 2013 ; Zhang and Zhou, 2012 ; Zhang et al, 2012 ; Hinai et al, 2013 ; Khokhrin et al, 2013 ; Lamba et al, 2014 ; Yuan et al, 2015 ; Hattinger et al, 2016 ; Powrozek et al, 2016 ; Chang et al, 2017 ) and none were genome wide association studies (GWAS). Key details of subject characteristics [e.g., ethnicity and inclusion criteria (Sprowl et al, 2012 )], type of chemotherapy regimens (Erculj et al, 2012 ; Sprowl et al, 2012 ; Powrozek et al, 2016 ), and nephrotoxicity criteria (Goekkurt et al, 2009 ; Kim et al, 2012 ; Khrunin et al, 2014 ) were not reported in some studies.…”
Section: Resultsmentioning
confidence: 99%
“…The study characteristics of the 28 articles included, all were candidate gene studies published between 2008 and 2017, are shown in Table 1 . Most were cohort studies (Wang et al, 2008 ; Filipski et al, 2009 ; Goekkurt et al, 2009 ; Chen et al, 2010 ; Khrunin et al, 2010a , 2012 , 2014 ; KimCurran et al, 2011 ; Tzvetkov et al, 2011 ; Erculj et al, 2012 ; Iwata et al, 2012 ; Windsor et al, 2012 ; Xu et al, 2012 , 2013 ; Zhang and Zhou, 2012 ; Zhang et al, 2012 ; Hinai et al, 2013 ; Khokhrin et al, 2013 ; Lamba et al, 2014 ; Yuan et al, 2015 ; Hattinger et al, 2016 ; Powrozek et al, 2016 ; Chang et al, 2017 ) and none were genome wide association studies (GWAS). Key details of subject characteristics [e.g., ethnicity and inclusion criteria (Sprowl et al, 2012 )], type of chemotherapy regimens (Erculj et al, 2012 ; Sprowl et al, 2012 ; Powrozek et al, 2016 ), and nephrotoxicity criteria (Goekkurt et al, 2009 ; Kim et al, 2012 ; Khrunin et al, 2014 ) were not reported in some studies.…”
Section: Resultsmentioning
confidence: 99%
“…The Newcastle-Ottawa Scale (NOS) was used to evaluated the quality of these included studies, based on a scoring system with three components: the selection of the subjects (0–4 points); the comparability of the study groups (0–2 points); the determination of the outcome of interest (treatment response) (0–3 points). The highest NOS score for each publication was 9 points, and in this meta-analysis, two studies had a NOS score of 9 [ 11 , 31 ]; 11 studies had a NOS score of 8 [ 8 – 10 , 12 , 13 , 15 , 16 , 20 , 25 , 26 , 30 ]; eight studies had a NOS score of 7 [ 2 , 7 , 14 , 19 , 21 , 24 , 28 , 29 ]; and two studies had a NOS score of 6 [ 23 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…(2015)Asian (China)246170/7664.3 (32–76)IIIA-IVDDP/CBP-basedOS, PFSPCR-RFLP XPG rs2296147 rs873601 113 Yuan, Z. J. (2015)Asian (China)4742/559 (29–74)III-IVDDP+GEMORDNA sequencing GSTP1 rs1695 114 Deng, J. H. (2015)Asian (China)9766/3157 (31–79)IIIB-IVDDP+GEM/NVP/TAX/DOCOR, PFSDNA pyrosequencing XRCC1 rs25487, GSTP1 rs1695 115 Shi, Z. H. (2015)Asian (China)240155/8561.5 (34–78)III-IVDDP+GEM/NVP/TAX/DOCOR, OSPCR-RFLP ERCC1 rs11615 rs3212986 rs2298881 116 Han, B. (2015)Asian (China)325116/209NRIIIB-IVDDP+GEM/NVP/TAX/DOCOR, OSPCR-RFLP XRCC1 rs25487 rs1799782 rs25489, GSTP1 rs1695 117 Li, P. (2015)Asian (China)14289/5362 (43–81)IIIB-IVDDP+NVPORPCR-RFLP XPD rs13181 rs1799793 118 Liu, J. Y.…”
Section: Resultsmentioning
confidence: 99%